2017
DOI: 10.1177/0034355217702136
|View full text |Cite
|
Sign up to set email alerts
|

Assessing College Life Adjustment of Students With Disabilities: Application of the PERMA Framework

Abstract: The clearest career path to the middle class generally involves access, and completion, of postsecondary education. For youth with disabilities, the knowledge and skills obtained through a college can limit the impact of a disability on obtaining high-quality employment. However, persons with disabilities are less likely to enroll in postsecondary education programs or graduate from those programs compared with their same-age peers without disabilities (Stodden, Stodden, Kim-Rupnow, Thai Nghi, & Galloway, 2003… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
52
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 56 publications
4
52
0
2
Order By: Relevance
“…Desde su descripción en el 2011, el modelo perma aumentó su presencia en el discurso psicológico, pero todavía no existe suficiente apoyo empírico del modelo (25). En los últimos años se han presentado estudios que miden este enfoque con ítems de escalas validadas de dimensiones específicas (26)(27)(28).…”
Section: Introductionunclassified
“…Desde su descripción en el 2011, el modelo perma aumentó su presencia en el discurso psicológico, pero todavía no existe suficiente apoyo empírico del modelo (25). En los últimos años se han presentado estudios que miden este enfoque con ítems de escalas validadas de dimensiones específicas (26)(27)(28).…”
Section: Introductionunclassified
“…Hence, a future replication and extension should be based on this conceptualization. Current research projects using the PERMA model demonstrate already promising results (e.g., Tansey et al, 2017;Wagner et al, 2020).…”
Section: Limitationsmentioning
confidence: 99%
“…Past research using the PERMA model found that high PERMA is negatively associated with PTSD, burnout, and depression [ 8 ]. The PERMA model was used to explain life satisfaction as a consequence among those with difficulties in life (e.g., individuals with disabilities) [ 9 ]. Psychological precedents (e.g., PTSD, burnout, and depression) and PERMA were significant factors associated with one another [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Psychological precedents (e.g., PTSD, burnout, and depression) and PERMA were significant factors associated with one another [ 8 ]. The PERMA model has also been employed to account for quality of life, life satisfaction, and sleep quality [ 9 ].…”
Section: Introductionmentioning
confidence: 99%